The Effect of COVID-19 Confinement in Behavioral, Psychological, and Training Patterns of Chess Players - Fuentes-García, Juan Pedro; Martínez Patiño, María José; Villafaina, Santos; Clemente-Suárez, Vicente Javier (Frontiers in Psychology, 2020)
The outbreak of the COVID-19 has triggered a pandemic, jeopardizing the global health. The sports world is also suffering the enormous consequences, such as the suspension of the Olympic Games in Tokyo or, in chess, the cancellation of the World Candidates Tournament 2020. Chess is a sport characterized by high psychophysiological demands derived from long training duration, tournaments, and games, leading to mental, emotional, and physical stress. These characteristics could provide chess players a certain advantage to face quarantine situations. This study aimed to analyze the effect of COVID-19 confinement in behavioral, psychological, and training patterns of chess players based on their gender, level of education, and level of chess gamed. We analyzed chess players (N: 450; age=38.12 ± 14.01 years) in countries where confinement was decreed: Professional players (N: 55; age=43.35 ± 13), high-performance players (N: 53; age=38.57 ± 13.46), competitive players (N: 284; age=36.82 ± 13.91) and amateur players (N: 58; age=39.10 ± 14.99). Results showed that chess players significantly decreased physical activity per day while increased chess practise during the confinement period. However, anxiety levels remained moderate despite the anti-stress effects of physical activity. Amateur players showed a significantly higher level of social alarm than professional and high-performance players. Moreover, professional players showed higher values of extraversion than high-performance players and amateur players. In neuroticism, professional players showed higher values than high-performance players. In addition, the professional players showed higher scores in psychological inflexibility than competitive players. Finally, chess players with the highest academic level showed higher levels of personal concern and anxiety due to the COVID-19 as well as lower psychological inflexibility compared to those with a lower academic level. In conclusion, chess players, especially those with a higher level, might have an adapted psychological profile to confinement situations and worrying levels of physical inactivity.